Evaluación de la variabilidad espacial de Black Carbon en un área urbana del Caribe colombiano (2019)
Black carbon (BC) is one of the air pollutants that most contributes to radiative forcing and climate change. It is emitted by the incomplete combustion of fossil fuels and biomass and can be used as a tracer of urban air pollution sources. In urban areas, BC variability is influenced by local sources, transport and weather conditions. However, for very complex urban environments, the use of mobile monitoring provides a better understanding of the dynamics of the contaminant. This study addresses the determination of BC concentrations using mobile and ambient real-time monitoring in Barranquilla. A microaethalometer (MA 200) and an aethalometer AE33 were used to obtain BC concentrations. The Ångström Absorption Exponent (AAE) for biomass burning and fossil fuels were determined for the study area. The results for ambient sampling show that vehicle traffic emissions prevail, but also with the influence of biomass burning. The average ambient BC concentration was 1.04 ± 1.03 µg/m3 and for mobile measurements was 16.1 ±16.5 µg/m3. The spatial distribution of BC concentrations shows that traffic emissions and congestion of vehicles, a consequence of road and transport infrastructure, are the factors that most affect BC concentrations. The meteorological variables had a significant influence on both mobile and environmental monitoring, mainly related to relative humidity and wind speed.